Transmembrane protease serine 5: a novel Schwann cell plasma marker for CMT1A. Issue 1 (12th December 2019) - Wang, Hongge; Davison, Matthew; Wang, Kathryn; Xia, Tai‐He; Kramer, Martin; Call, Katherine; Luo, Jun; Wu, Xingyao; Zuccarino, Riccardo; Bacon, Chelsea; Bai, Yunhong; Moran, John J.; et al.
Abstract: Objective: Development of biomarkers for Charcot‐Marie‐Tooth (CMT) disease is critical for implementing effective clinical trials. The most common form of CMT, type 1A, is caused by a genomic duplication surrounding the PMP22 gene. A recent report (Neurology 2018;90:e518–3524) showed elevation of neurofilament light (NfL) in plasma of CMT1A disease patients, which correlated with disease severity. However, no plasma/serum biomarker has been identified that is specific to Schwann cells, the most directly affected cells in CMT1A. Methods: We used the Olink immuno PCR platform to profile CMT1A patient ( n = 47, 2 cohorts) and normal control plasma ( n = 41, two cohorts) on five different Olink panels to screen 398 unique proteins. Results: The TMPRSS5 protein (Transmembrane protease serine 5) was elevated 2.07‐fold ( P = <0.0001) in two independent cohorts of CMT1A samples relative to controls. TMPRSS5 is most highly expressed in Schwann cells of peripheral nerve. Consistent with early myelination deficits in CMT1A, TMPRSS5 was not significantly correlated with disease score (CMTES‐R, CMTNS‐R), nerve conduction velocities (Ulnar CMAP, Ulnar MNCV), or with age. TMPRSS5 was not significantly elevated in smaller sample sets from patients with CMT2A, CMT2E, CMT1B, or CMT1X. The Olink immuno PCR assays confirmed elevated levels of NfL (average 1.58‐fold, P < 0.0001), which correlated with CMT1A patient disease score. Interpretation: These data identify the first Schwann cell‐specific protein that is elevated in plasma of CMT1A patients, and may provide a disease marker and a potentially treatment‐responsive biomarker with good disease specificity for clinical trials.